2022
DOI: 10.1186/s12987-022-00380-6
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated amyloid angiopathy and related vascular alterations in a mixed murine model of Alzheimer´s disease and type two diabetes

Abstract: Background While aging is the main risk factor for Alzheimer´s disease (AD), emerging evidence suggests that metabolic alterations such as type 2 diabetes (T2D) are also major contributors. Indeed, several studies have described a close relationship between AD and T2D with clinical evidence showing that both diseases coexist. A hallmark pathological event in AD is amyloid-β (Aβ) deposition in the brain as either amyloid plaques or around leptomeningeal and cortical arterioles, thus constituting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 79 publications
1
7
0
Order By: Relevance
“…In fact, in our murine models of AD-T2D and AD-T1D, the levels of serum Aβ were reduced, indicating the inability to expel peptides from the CNS across the blood–brain barrier, while intracerebral soluble Aβ levels were increased [ 78 , 79 ]. In fact, the higher levels of soluble Aβ40 and 42 in the CNS observed in T1D and T2D are also in agreement with large synaptic loss and neuronal death observations [ 79 , 81 , 162 , 163 , 164 , 165 , 166 ]. It is feasible that the shift toward more toxic soluble species might contribute to the observed progressive synapse reduction in prediabetic and diabetic AD mice [ 50 , 167 ] and an in silico study [ 168 ].…”
Section: Link Between Diabetes Mellitus Alzheimer’s Disease and Vascu...supporting
confidence: 86%
See 2 more Smart Citations
“…In fact, in our murine models of AD-T2D and AD-T1D, the levels of serum Aβ were reduced, indicating the inability to expel peptides from the CNS across the blood–brain barrier, while intracerebral soluble Aβ levels were increased [ 78 , 79 ]. In fact, the higher levels of soluble Aβ40 and 42 in the CNS observed in T1D and T2D are also in agreement with large synaptic loss and neuronal death observations [ 79 , 81 , 162 , 163 , 164 , 165 , 166 ]. It is feasible that the shift toward more toxic soluble species might contribute to the observed progressive synapse reduction in prediabetic and diabetic AD mice [ 50 , 167 ] and an in silico study [ 168 ].…”
Section: Link Between Diabetes Mellitus Alzheimer’s Disease and Vascu...supporting
confidence: 86%
“…It is feasible that the shift toward more toxic soluble species might contribute to the observed progressive synapse reduction in prediabetic and diabetic AD mice [ 50 , 167 ] and an in silico study [ 168 ]. In addition, prediabetes and T2D promote an increased accumulation of Aβ in the form of amyloid angiopathy (AAC) around blood vessels [ 81 ], which is associated with an increased risk of vascular rupture [ 169 ]. On the other hand, Aβ clearance might also be affected.…”
Section: Link Between Diabetes Mellitus Alzheimer’s Disease and Vascu...mentioning
confidence: 99%
See 1 more Smart Citation
“…This deposition of Aβ in brain vessel walls is a common pathological finding in older people, it is the hallmark of CAA and has also been closely related with AD. In vivo multiphoton imaging in AD mice also showed that this vascular amyloid pathology occurs in an age‐dependent manner (Dong et al, 2010) and is further accelerated by the presence of diabetes (Vargas‐Soria et al, 2022). In fact, over 80–90% of AD patients present CAA (DeSimone et al, 2017a), which is indeed associated with the presence of the APOE‐ε4 allele, hypercholesterolemia and history of stroke (Brenowitz et al, 2015).…”
Section: Vascular Dysfunction In Admentioning
confidence: 99%
“…Cerebrovascular health is essential for vascular clearance of Aβ and alterations in neurovascular function have been implicated in CAA [2]. Suppression of the ability of neural activity to increase cerebral blood ow (CBF) (functional hyperemia), a fundamental homeostatic response of the cerebral microcirculation [15], occurs early in patients with CAA [16][17][18], whereas Aβ-induced suppression of functional hyperemia and dysfunction of the endothelial regulation of CBF have been linked to CAA in mouse models [13,[19][20][21]. Aβ-induced vascular oxidative stress and the attendant neurovascular dysregulation and damage have emerged as key factors in CAA both in mouse models [19,20] and in humans [22].…”
mentioning
confidence: 99%